Laser induced desorption and ablation: mechanism of metal removal from an Al-Cu-Fe alloy and a quasicrystal of the same composition - Mauro Satta; Haichen Liu; Xianglei Mao; Giuliano Moretti; Richard E. Russo; Anna Giardini; Aldo Mele (International Journal of Photoenergy)
Quasicrystals are a special class of metallic alloys that share some of the properties of crystals. Their structures reduce to a single repeating unit like that of the unit cell of a crystal. The quasi-unitcell is representative of a cluster like structure where electrons cannot move with freedom as in metals. Quasicrystals are formed of metallicelements but they do not have metallic properties.